Gas heating and plasma expansion in pulsed microwave-excited microplasmas. (10th August 2015) - Hoskinson, Alan R; Yared, Alexander; Hopwood, Jeffrey
Abstract: Microwave resonators are used to generate microplasmas in atmospheric-pressure argon and helium. We present observations of the transient behavior of a microplasma after a fast increase in power, including time-resolved photography and spectroscopic gas temperature measurements. The results show that in argon both plasma filamentation and gas heating continue out to millisecond time scales, while helium microplasmas reach steady-state conditions after a few microseconds.